Study The Result Involution Graph For The Janko Group J4 - Ali Aubaid; Ahmed Arkan Meteab (Wasit Journal for Pure Sciences, 2023)
Consider a finite group G, and define I(G) as a collection of the involution elements in G. The simple undirected graph with vertex set being the elements of G with two vertices x, y ∈ G are adjacent if x ≠ y and  xy  in I(G),  is  called  the result involution graph  and denoted by $Gamm RI_G$. In this work, we investigate the structure of the result  involution graphs for  the Janko groups J4  to obtain certain number of graph attributes.